Implementation of the Price Management Information System (SIMAHAR) Application in Proposing Standard Prices for Goods and Services at the Regional Finance and Asset Agency of West Kutai Regency - Aina Khilya Isna Shofia; M. Mas'ud Said; Rulam Ahmadi (LP2M IAIN Palopo, 2026)
The development of information technology in the era of globalization has encouraged local governments to undertake digital transformation in financial management to improve efficiency, transparency, and accountability. This study aims to analyze the implementation of the Price Management Information System (SIMAHAR) application in the process of proposing standard prices for goods and services at the Regional Finance and Asset Agency (BKAD) of West Kutai Regency. The study focuses on implementation steps and strategies, the roles of the actors involved, implementation results, and factors hindering SIMAHAR implementation. This research used a qualitative method with a descriptive approach. Data were obtained through structured interviews with officials and staff of the BKAD of West Kutai Regency, as well as representatives from several relevant Regional Work Units (SKPD). Data analysis was conducted systematically to understand the dynamics of implementation and factors influencing the effectiveness of SIMAHAR implementation. The results show that the implementation of SIMAHAR has had a positive impact in accelerating the price standard proposal process, improving data accuracy, and minimizing the potential for price manipulation. Previously, the proposal process was carried out manually using physical documents, which was time-consuming and prone to errors. Through SIMAHAR, proposals become more effective, transparent, and accountable because they are equipped with comparative documents and price links that can verify accuracy. SIMAHAR implementation involves the crucial roles of the Regional Government Agency (BKAD) as the system manager, Regional Government Agencies (SKPD) as data inputters, and internal auditors as accountability monitors. However, several obstacles remain, including limited communication between SKPDs, lack of training, unstable internet connections, and user resistance to technological change. Overall, SIMAHAR makes a significant contribution to supporting the principles of good governance in regional financial management. This study recommends strengthening technological infrastructure, increasing human resource capacity, and optimizing coordination between SKPDs to achieve more optimal implementation.